The Effect of Aerobic Training Program on Cardiopulmonary Parameters and Oxygen Saturation in Elite Judokas - Önder Dağlıoğlu; Tugay Yılmaz (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to examine the effect of aerobic training program on cardiopulmonary parameters and oxygen saturation in elite judokas. Total of 22 male elite judokas, aged between 18 and 25 participated in the study voluntarily. Subjects were randomly divided into two groups as experimental group (n=11, age:21.60±2.06) and control group (n=11, age:20.50±1.77). The experimental group was given an aerobic exercise program for 3 days a week for 8 weeks. Before and after the aerobic exercise program, body weight, body mass index (BMI), body fat percentage (BF%), systolic blood pressure (SBP), diastolic blood pressure (DBP), resting heart rate (RHR), maximal heart rate (HRmax), maximal work rate (WRmax), maximal minute ventilation (VEmax)  and maximal oxygen consumption capacity (VO2max) were measured. Individual oxygen consumption capacities were determined using the Ramp protocol in the gas analysis system. Paired Sample t test was used for intra-group comparison and Independent Sample t test was used for statistical analysis of the data. The level of significance was determined as p lt;0.05. When the pre-test and post-test results of the aerobic training program applied to the experimental group were compared, p lt;0.05 significance was found in the experimental group, SBP, DBP, RHR, HRmax, %BF, VO2max, WRmax, VEmax and SpO2 values. Significant differences were found between the groups in favor of the experimental group (p lt;0.05) for SBP, DBP, RHR, HRmax, WRmax, VEmax, VO2max and SpO2 values. It can be said that the aerobic training program applied to the judokas has a positive effect on cardiopulmonary parameters and oxygen saturation.